Wskazywanie w myślach. Myśli zależne od przedmiotu a semantyka złożonych wyrażeń wskazujących - Tarnowski, Maciej (Filozofia Nauki, 2020)
In this article, I investigate the relation between the concept of object-dependent thoughts (ODTs) and the semantics of complex demonstratives. I begin by showing that a strong syntactic version of ODTs proposed by Adams and colleagues suffers from problems similar to those plaguing several semantic theories (Richard 1993, Larson, Segal 1995). Next, I turn to Eros Corazza’s counterproposal of perspectival thoughts and investigate whether it can provide us with promised explanatory benefits. I conclude by formulating an alternative picture of ODTs based on Evans’ work and showing that it successfully handles the problems posed for semantics of complex demonstratives. In order to do this, I introduce and defend a view of individual perceptive concepts that may serve as a mental counterpart of demonstration.